2017
DOI: 10.1007/s40145-017-0246-0
|View full text |Cite
|
Sign up to set email alerts
|

d–f luminescence of Ce3+ and Eu2+ ions in BaAl2O4, SrAl2O4 and CaAl2O4 phosphors

Abstract: Ce 3+ and Eu 2+ doped alkaline earth aluminates MAl 2 O 4 (M = Ca, Sr, Ba) were prepared by single-step combustion synthesis at low temperature (600 ℃).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…The molar absorption coefficients (e) of Eu-1 at 273 nm and 336 nm are 569 L mol À1 cm À1 and 163 L mol À1 cm À1 , respectively, and e of Eu-2 at 405 nm is 4046 L mol À1 cm À1 , which is consistent with the absorbance intensity corresponding to the 4f-5d transition in Eu II complexes reported in the previous work. [15] The Eu-1 solution showed a bright green emission with l max of 512 nm, an excited state decay lifetime of 332 ns, and a PLQY of 15 %. Meanwhile, the Eu-2 solution showed an orange emission with l max of 590 nm, an excited state decay lifetime of 167 ns, and a PLQY of 8 %.…”
mentioning
confidence: 94%
“…The molar absorption coefficients (e) of Eu-1 at 273 nm and 336 nm are 569 L mol À1 cm À1 and 163 L mol À1 cm À1 , respectively, and e of Eu-2 at 405 nm is 4046 L mol À1 cm À1 , which is consistent with the absorbance intensity corresponding to the 4f-5d transition in Eu II complexes reported in the previous work. [15] The Eu-1 solution showed a bright green emission with l max of 512 nm, an excited state decay lifetime of 332 ns, and a PLQY of 15 %. Meanwhile, the Eu-2 solution showed an orange emission with l max of 590 nm, an excited state decay lifetime of 167 ns, and a PLQY of 8 %.…”
mentioning
confidence: 94%
“…2(b). Two broad absorption bands centered at 340 and 445 nm were ascribed to the 4f-5d 1 and 4f-5d 2 transitions of Ce 3+ ion, respectively [29,30]. Besides the intrinsic absorption bands of Ce 3+ ion, the absorption centered at 430 and 596 nm could be observed from all the Cr 3+ ion doped samples, corresponding to the 4 A 2 -4 T 1 and 4 A 2 -4 T 2 transitions of Cr 3+ ion, respectively [31].…”
Section: Resultsmentioning
confidence: 90%
“…There are various types of strontium aluminate hosts, such as 19 has a magnetoplumbite structure [28,29]. Among these, SrAl 2 O 4 is a promising host material for ensuring persistent luminescence and acts as a convenient host crystal for rare-earth and transition metal dopants [30]. It was found that the luminescent center is the same, but excitation processes are different at different temperatures.…”
Section: Strontium Aluminate Phosphorsmentioning
confidence: 99%
“…During this process, Eu 3+ is reduced to Eu 2+ in a reducing atmosphere; various reductants, such as H2 + N2, HI, and NH4I, are employed to facilitate this. The reductive atmosphere is crucial for avoiding sample decomposition [30] under Creative Commons Attribution (CC BY) license.…”
Section: Synthesis Of Strontium Aluminate Phosphorsmentioning
confidence: 99%